STRATEGIC MONITORING AS AN IMPORTANT MECHANISM FOR INCREASING THE EFFICIENCY OF MANAGEMENT IN HIGHER EDUCATIONAL INSTITUTIONS - Abdulla Mahmudovich Magrupov (Galaxy International Interdisciplinary Research Journal, 2023)
The article deals with transformational processes in education, the transformation of higher education, strategic management, strategic monitoring mechanisms, as well as determining the vector of strategic development of a university in a changing environment, digital monitoring technologies.